High-Throughput Analysis of Total Plasma Fatty Acid Composition with Direct In Situ Transesterification - Glaser, Claudia; Demmelmair, Hans; Koletzko, Berthold (PLOS ONE, 2010)
Background Plasma fatty acid (FA) composition reflects dietary intake and endogenous turnover and is associated with health outcomes on a short and long term basis. The total plasma FA pool represents the composition of all FA containing lipid fractions. We developed a simplified and affordable high-throughput method for the analysis of total plasma FA composition, suitable for large studies. Methodology/Principal Findings The total lipid FA from 100 µl plasma is transferred in situ into methyl esters, avoiding initial extraction and drying steps. The fatty acid methyl esters are extracted once and analyzed by gas chromatography. For the new direct in situ transesterification method optimal, reaction parameters were determined. Intra-assay analysis (n = 8) revealed coefficients of variation below 4% for FA contributing more than 1% to total FA. Conclusions/Significance The results show good agreement with FA concentrations obtained by a reference method. The new direct in situ transesterification method is robust and simple. Sample preparation time and analysis costs are reduced to a minimum. This method is an economically and ecologically superior alternative to conventional methods for assessing plasma FA status in large studies.